2017
DOI: 10.18632/oncotarget.17581
|View full text |Cite
|
Sign up to set email alerts
|

Local immune response depends on p16INK4a status of primary tumor in vulvar squamous cell carcinoma

Abstract: BackgroundThe p16Ink4a is not a surrogate marker for high-risk human papilloma virus (HPV) genotypes but indicates better prognosis in vulvar squamous cell carcinoma patients. Our recent study confirmed substantial mismatch between p16Ink4a and high-risk HPV-status as well as revealed that p16Ink4a-overexpression itself is an independent prognostic factor for vulvar cancer.AimTo determine significance of the tumor infiltrating immune cells and p16Ink4a–status for better outcome of patients with vulvar cancer.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Recently we have reported that p16 INK4a -overexpression modulates immune cells infiltration regardless to (hr)HPV-DNA status [ 5 ]. Patients with p16 INK4a -negative tumors although more infiltrated with TILs (CD8+, CD4+, GZB+ cells) had worse outcome than cases with p16 INK4a -positive vSCCs [ 5 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently we have reported that p16 INK4a -overexpression modulates immune cells infiltration regardless to (hr)HPV-DNA status [ 5 ]. Patients with p16 INK4a -negative tumors although more infiltrated with TILs (CD8+, CD4+, GZB+ cells) had worse outcome than cases with p16 INK4a -positive vSCCs [ 5 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently we have reported that p16 INK4a -overexpression modulates immune cells infiltration regardless to (hr)HPV-DNA status [ 5 ]. Patients with p16 INK4a -negative tumors although more infiltrated with TILs (CD8+, CD4+, GZB+ cells) had worse outcome than cases with p16 INK4a -positive vSCCs [ 5 , 15 ]. Here CC-PD-L1 expression was frequently observed on more infiltrated p16 INK4a -negative vSCCs suggesting that anti-immune programmed death-ligand 1 (PD-L1) pathway is at least partially responsible for worse outcome in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, IFN-γ, produced by TILs, seems not to be the main reason for the difference of PD-L1 expression between HPV positive and negative anogenital cancer patients, because no signi cant difference was identi ed in numbers of CD8 + TILs distributing in HPV positive and negative anal and cervical cancer patients [38,39]. In vulvar SCC, there was fewer number of CD8 + TILs in p16 positive cases compared with p16 negative [40]. Therefore, genetic background (genomic aberrations and aberrant oncogenic signaling) may take the primary responsibility for PD-L1 overexpression in anogenital cancers [17,41].…”
Section: Discussionmentioning
confidence: 95%